Analysis of proximal bone margins in diabetic foot osteomyelitis by conventional culture, DNA sequencing and microscopy. Issue 10 (28th August 2019) - Malone, Matthew; Fritz, Blaine G.; Vickery, Karen; Schwarzer, Saskia; Sharma, Varun; Biggs, Nathan; Radzieta, Michael; Jeffries, Thomas T.; Dickson, Hugh G.; Jensen, Slade O.; Bjarnsholt, Thomas
Abstract : Multiple approaches were employed to detect pathogens from bone margins associated with Diabetic Foot Osteomyelitis (DFO). Intra‐operative bone specimens of 14 consecutive subjects with suspected DFO were collected over a six‐month study period from Liverpool Hospital. Infected bone and a proximal bone margins presumed to be 'clean/non‐infected' were collected. Bone material was subjected to conventional culture, DNA sequencing and microscopy. In total, eight of 14 (57%) proximal bone margins had no growth by conventional culture but were identified in all proximal bone specimens by DNA sequencing. Proximal margins had lower median total microbial counts than infected specimens, but these differences were not statistically significant. Pathogens identified by sequencing in infected specimens were identified in proximal margins and the microbiomes were similar (ANOSIM = 0.02, p = 0.59). Using a combination of SEM and/or PNA‐FISH, we visualized the presence of microorganisms in infected bone specimens and their corresponding proximal margins of seven patients (50%) with DFO. We identify that bacteria can still reside in what seems to be proximal 'clean' margins. The significance and implications of clinical outcomes requires further analysis from a larger sample size that incorporates differences in surgical and post‐operative approaches, correlating any outcomes back to culture‐sequence findings.